1999
DOI: 10.1128/mcb.19.10.7181
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPβ Modulates the Early Events of Keratinocyte Differentiation Involving Growth Arrest and Keratin 1 and Keratin 10 Expression

Abstract: The epidermis is a stratified squamous epithelium composed primarily of keratinocytes that become postmitotic and undergo sequential changes in gene expression during terminal differentiation. The expression of the transcription factor CCAAT/enhancer binding protein ␤ (C/EBP␤) within mouse epidermis and primary keratinocytes has recently been described; however, the function of C/EBP␤ within the epidermal keratinocyte is unknown. We report here that transient transfection of mouse primary keratinocytes with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
121
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(127 citation statements)
references
References 62 publications
6
121
0
Order By: Relevance
“…The present results are consistent with a model wherein C/EBP␣ enhances hINV gene expression. In contrast, C/EBP␤ and ␦ inhibits hINV expression in cultured cells (15) or does not influence hINV expression in C/EBP␤ knockout mice (38). This may, at least in part, explain why hINV is expressed in the suprabasal epidermal layers, where C/EBP␣ is expressed, and not in the basal layers, where C/EBP␤ predominates.…”
Section: Figmentioning
confidence: 74%
See 1 more Smart Citation
“…The present results are consistent with a model wherein C/EBP␣ enhances hINV gene expression. In contrast, C/EBP␤ and ␦ inhibits hINV expression in cultured cells (15) or does not influence hINV expression in C/EBP␤ knockout mice (38). This may, at least in part, explain why hINV is expressed in the suprabasal epidermal layers, where C/EBP␣ is expressed, and not in the basal layers, where C/EBP␤ predominates.…”
Section: Figmentioning
confidence: 74%
“…They begin as proliferative cells and are ultimately converted to nonproliferating cells called corneocytes that assemble the epidermal surface (12). This change involves a remarkable number of gene activation events that result in the expression of a group of proteins, including involucrin, that are designed to construct this barrier (12,37,38). Specific PKC isoforms are implicated in this process.…”
Section: Novel Pkc Isoforms Drive Keratinocyte Differentiation Viamentioning
confidence: 99%
“…Epidermis was removed from the dermis as described (Oh and Smart, 1998) and all organs/tissues were homogenized in RIPA buffer containing 1% NP-40, 0.5% sodium deoxycholate, 0.1% SDS, pH 7.4, 1 mM PMSF, 1 mM SOV, 1 Â GIBCO complete protease inhibitor cocktail. Samples (20 mg) were separated by SDS-PAGE and western analysis was conducted as described (Zhu et al, 1999). (b) Immunohistochemical staining for C/EBPb in skin of wild type and (c) K5-Cre;C/EBPb fl/fl mice.…”
mentioning
confidence: 99%
“…C/EBPb is expressed in many tissues, including epidermis (Maytin and Habener, 1998;Oh and Smart, 1998) where it plays a role in the early stages of stratified squamous differentiation (Zhu et al, 1999). Recent studies have identified a role for C/EBPb in tumor development (Zhu et al, 2002), senescence (Sebastian et al, 2005), cell survival (Buck et al, 2001;Zhu et al, 2002;Wessells et al, 2004;Li et al, 2005) and cellular transformation (Zhu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have identified a role for C/EBPb in tumor development (Zhu et al, 2002), senescence (Sebastian et al, 2005), cell survival (Buck et al, 2001;Zhu et al, 2002;Wessells et al, 2004;Li et al, 2005) and cellular transformation (Zhu et al, 2002). In terms of cell transformation, C/EBPb can cooperate with Ras12V to transform NIH3T3 cells (Zhu et al, 1999) and more recently, it has been shown that cell-cycledependent phosphorylation of C/EBPb on Ser64 and Thr189 is required to promote Ras-induced transformation of NIH3T3 cells (Shuman et al, 2004).…”
Section: Introductionmentioning
confidence: 99%